2022
DOI: 10.1186/s12989-022-00499-2
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic quality evaluation and review of nanomaterial genotoxicity studies: a regulatory perspective

Abstract: The number of publications in the field of nanogenotoxicology and the amount of genotoxicity data on nanomaterials (NMs) in several databases generated by European Union (EU) funded projects have increased during the last decade. In parallel, large research efforts have contributed to both our understanding of key physico-chemical (PC) parameters regarding NM characterization as well as the limitations of toxicological assays originally designed for soluble chemicals. Hence, it is becoming increasingly clear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…To assure this, the OECD 487 guidelines propose two parameters, named cytokinesis-block proliferation (CBPI) and replication (RI) indexes, to indicate cell proliferation and the number of cell cycles, respectively, during the time exposure to cytochalasin B [ 14 ]. It was established that CBPI values higher than 1.5 and RPI values higher than 55% were indicative of a low cytostatic effect of the sample under evaluation [ 14 , 20 , 21 ]. Considering the results described in Table 3 and Table 4 , the CBPI and RI values observed for MMS (lower in the first experiment in comparison to the second) may explain why MMS, at the same concentration, induced different rates of increase in CBMN.…”
Section: Discussionmentioning
confidence: 99%
“…To assure this, the OECD 487 guidelines propose two parameters, named cytokinesis-block proliferation (CBPI) and replication (RI) indexes, to indicate cell proliferation and the number of cell cycles, respectively, during the time exposure to cytochalasin B [ 14 ]. It was established that CBPI values higher than 1.5 and RPI values higher than 55% were indicative of a low cytostatic effect of the sample under evaluation [ 14 , 20 , 21 ]. Considering the results described in Table 3 and Table 4 , the CBPI and RI values observed for MMS (lower in the first experiment in comparison to the second) may explain why MMS, at the same concentration, induced different rates of increase in CBMN.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, how these TGs can be/are implemented in practice is problematic because of omissions in nano-specific data requirements. For example, often adequate nanomaterial physicochemical characterization data are not provided; in which case a regulatory evaluator is not able to correlate what exactly the test material was with the nanomaterial under assessment [ 45 ]. This in turn makes it difficult to determine if the same nanomaterial was tested across a battery of assays where datasets are provided on different genotoxicity endpoints.…”
Section: Outcomes From the Roundtable Discussionmentioning
confidence: 99%
“…However, none of the studies considered in this review were conducted through the respiratory exposure route, which is one of the most relevant regarding nanomaterial exposure [ 38 ]. When focussing on the respiratory route, a more recent review found that positive outcomes were reported with TiO 2 nanoparticles, whereas nanofibres (mainly carbon nanotubes) recorded negative results [ 45 ]. On the other hand, Horibata et al focussed on genotoxicity studies performed with Mitsui-7, the only multiwalled carbon nanotube that has been classified as a possible carcinogen to humans (Group 2B) [ 46 , 47 ].…”
Section: The In Vivo Micronucleus Assaymentioning
confidence: 99%
“…org/ 10. 1186/ s12989-022-00499-2 Following publication of the original article [1], the authors reported an error in the name of the first author, it should change from "Kirsi K. Siivola" to "Kirsi M. Siivola".…”
Section: Publisher's Notementioning
confidence: 99%